Datasets for dependency tree reranking - Do, Bich-Ngoc; Rehbein, Ines (Universität, 2023)
This resource contains the datasets for dependency tree reranking in 3 languages: English, German and Czech. The creation, analysis and experiment results of the datasets are described in the paper: Do and Rehbein (2020). "Neural Reranking for Dependency Parsing: An Evaluation".
Produktionsdatum: 2020
Gesehen am 22.11.2023
Keywords: Forschungsdaten; Datenbank